Commentary on Transendent Mind by Barušs and Mossbridge - Broderick, Damien (Journal of Scientific Exploration, 2018)
Half a lifetime ago, George Lakoff and Mark Johnson dismantled one of the mental tools we use to understand our reality, usually bamboozling ourselves in the process. Their classic study Metaphors We Live By (1980) showed how powerfully certain very basic physical parameters bracket our emotional response to the world and other people. One routine metaphor draws on height as a privileged characteristic: her Highness, ascending a hierarchy, sheer physiological tallness as a marker of worth and attractiveness. So what metaphors and metonymies are invoked by the term “transcendent mind”? Doesn’t it immediately exert a claim on us of superior worth, purified of dross, even unearthly magnificence? Certainly that is suggested by the Oxford Dictionary, which finds “transcendent” to convey “surpassing the ordinary; exceptional, existing apart from and not subject to the limitations of the material universe,” and even, drawing on Kant, “not realizable in experience.” On the whole, then, a transcendent mind would be far more wonderful than the coarse, grubby, workaday thinking and feeling unit tucked away under our skulls. Look at the roots of the word, it’s that height thing again: from the Latin verb transcendere, “climbing up and over.” Then again, haven’t I just glibly tossed in another standard metaphor for mind, that it’s a kind of mechanism, a “workaday thinking and feeling unit,” a sort of neural abacus? I admit it. Contemporary science finds no use for the traditional hypothesis of an immaterial soul extended downward to the world of stuff from an empyreal beyond, infusing the flesh and working the mindless physical abacus.